THE EFFECTIVENESS OF CONTEXTUAL GRAMMAR-BASED LEARNING IN IMPROVING THE WRITING SKILLS OF THIRD-SEMESTER STUDENTS AT POLITEKNIK ALKON KALIMANTAN - Rochman, Muhammad; Widjajanti, Suzanna (Prologue: Journal on Language and Literature, 2026)
This study aims to investigate the effectiveness of contextual grammar-based learning in improving the writing skills of third-semester students at Politeknik Alkon Kalimantan. This research employed a quantitative pre-experimental design using a one-group pretest-posttest method. The participants consisted of third-semester students enrolled in an English course. Data were collected through writing tests administered before and after the implementation of contextual grammar-based learning. The treatment involved integrating grammar instruction with contextual and practical writing tasks relevant to students’ academic and vocational needs. The collected data were analyzed using descriptive and inferential statistics to measure the improvement in students’ writing performance. The findings revealed that students' writing skills improved significantly after the implementation of contextual grammar-based learning. The results showed an increase in students’ ability to apply correct grammatical structures, organize ideas coherently, and develop more accurate sentences in writing. Therefore, contextual grammar-based learning was found to be effective in enhancing students’ writing skills. This study suggests that contextual grammar-based learning can be implemented as an alternative teaching strategy to improve writing competence among vocational higher education students.